Uniśa śatakera madhyaśreṇī o Bāṅalā sāhitya - Haka, Ābula Kāsema Phajalula, 1944- (Khāna Brādārsa, 1979)
On the Bengali middle class people and Bengali literature of the nineteenth century; historical study.